2012
DOI: 10.4049/jimmunol.1200465
|View full text |Cite
|
Sign up to set email alerts
|

Ablation of Leptin Receptor-Mediated ERK Activation Impairs Host Defense against Gram-Negative Pneumonia

Abstract: The adipocyte-derived hormone, leptin, plays an important role in regulating energy homeostasis and the innate immune response against bacterial infections. Leptin’s actions are mediated by signaling events initiated by phosphorylation of tyrosine residues on the long form of the leptin receptor. We recently reported that disruption of leptin receptor mediated STAT3 activation augmented host defense against pneumococcal pneumonia. In this report, we assessed leptin receptor mediated ERK activation, a pathway t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 46 publications
2
17
0
Order By: Relevance
“…While in dendritic cells, TREM-2/DAP12 stimulation is through activation of ERK, but independent of NF-jB and P38 stress-activated protein kinase [52]. Studies have demonstrated that Akt is required in the killing of Neisseria gonorrhoeae [29] and Erk is involved in host defence against Klebsiella pneumoniae [54], whereas JNK is reported to inhibit macrophage killing of Staphylococcus aureus [55] and p38 is shown to attenuate macrophage antibacterial activities against Streptococcus pneumoniae [56]. Our data showed that silencing of TREM-2 inhibited Akt phosphorylation, but had no effect on activation of ERK, P38 and JNK.…”
Section: Discussionmentioning
confidence: 99%
“…While in dendritic cells, TREM-2/DAP12 stimulation is through activation of ERK, but independent of NF-jB and P38 stress-activated protein kinase [52]. Studies have demonstrated that Akt is required in the killing of Neisseria gonorrhoeae [29] and Erk is involved in host defence against Klebsiella pneumoniae [54], whereas JNK is reported to inhibit macrophage killing of Staphylococcus aureus [55] and p38 is shown to attenuate macrophage antibacterial activities against Streptococcus pneumoniae [56]. Our data showed that silencing of TREM-2 inhibited Akt phosphorylation, but had no effect on activation of ERK, P38 and JNK.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously used leptin receptor mutant mice (s/s and l/l) to identify which LepRb-mediated intracellular signaling events contribute to the host response to bacterial pneumo-nia (35,36). Using the s/s mouse, which cannot signal through the LepRb¡-STAT3 pathway and is obese, we observed that leptin-mediated ERK activation enhances AM leukotriene (LT) synthesis, AM phagocytosis, and bacterial killing, resulting in protection against pneumococcal pneumonia in vivo (36).…”
Section: Introductionmentioning
confidence: 99%
“…A synergetic role for GM-CSF and osteopontin in the recruitment of macrophages and monocytes to the implanted kidney, which promotes remodeling and better engraftment, is conceivable. A possible mechanism skewing infiltrated monocytes to M2 (regenerative) macrophages to promote IF is supported by the lower leptin levels in this group, as, besides an "energy indicator," leptin has been reported to promote a proinflammatory environment and skew macrophages toward the inflammatory M1 phenotype, either directly or through mast cells (40)(41)(42)(43).…”
Section: Discussionmentioning
confidence: 86%